A Study of the Dielectric Constant of Potassium Hexacyanoferrate Trihydrate - Chakrabarti, S. K.; Jha, I. S.; Yadav, R. N. (Journal of Nepal Chemical Society, 2013)
The variation of dielectric constant with temperature of potassium hexacyanoferrate trihydrate has been reported in this study. It is a monoclinic ferroelectric crystal. As the temperature is gradually increased a jump in the value of its dielectric constant takes place around 57°C. But as the temperature crosses 145°C, the dielectric constant increased drastically giving two adjacent peaks at 154°C and 157°C. In course of cooling also the dielectric constant of it shows anomaly–however in diminished order. Such anomalous behaviour of the dielectric constant of potassium hexacyanoferrate trihydrate may be mainly due to its high sensitivity to mechanical stresses, thereby causing piezoelectricity. DOI: http://dx.doi.org/10.3126/jncs.v29i0.9249 Journal of Nepal Chemaical Society Vol. 29, 2012 Page : 58-61 Uploaded date: 12/4/2013